2022
DOI: 10.14202/vetworld.2022.1727-1737
|View full text |Cite
|
Sign up to set email alerts
|

Assessing farm biosecurity and farmers' knowledge and practices concerning antibiotics and antibiotic resistance in poultry and pig farms in Southern Togo

Abstract: ackground and Aim: Several factors contribute to the unusual incidence of antibiotic resistance, which is now a primary public health concern. However, failure in managing preventive and therapeutic antibiotic use on farms is one of the most crucial factors. Therefore, this study aimed to evaluate the biosecurity of farms, farmers' competence, and practices related to antibiotics and their resistance in poultry and pig rearing in Togo. Materials and Methods: Through a cross-sectional survey, 121 commercial po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…For example, in many countries including North America, asymptomatic calves are administered macrolides for prophylaxis or metaphylaxis of bovine respiratory disease (BRD) (Cameron and McAllister 2016 ). Widespread across low- and middle-income countries, with specific interests in the SSA region, is the prophylactic use of antibiotics in animal production (Moffo et al 2020 ; Mdegela et al 2021 ; Adebowale et al 2022 ; Bedekelabou et al 2022 ). Enforcing this practice is the increasing demand for animal protein from a rapidly growing population (Mankhomwa et al 2022 ).…”
Section: Prophylactic Use Of Antimicrobialsmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, in many countries including North America, asymptomatic calves are administered macrolides for prophylaxis or metaphylaxis of bovine respiratory disease (BRD) (Cameron and McAllister 2016 ). Widespread across low- and middle-income countries, with specific interests in the SSA region, is the prophylactic use of antibiotics in animal production (Moffo et al 2020 ; Mdegela et al 2021 ; Adebowale et al 2022 ; Bedekelabou et al 2022 ). Enforcing this practice is the increasing demand for animal protein from a rapidly growing population (Mankhomwa et al 2022 ).…”
Section: Prophylactic Use Of Antimicrobialsmentioning
confidence: 99%
“…Findings from a similar study in southern Togo showed that poultry farmers (93%) utilized antibiotics in production more than pig farmers (50%). About 84% of the farmers who consented to antimicrobial use utilized them as prophylaxis in the production of poultry and pigs (Bedekelabou et al 2022 ). Almost all the farmers (98%) recruited in the study reportedly failed to consult a veterinarian for proper clinical and laboratory diagnosis as well as antibiotic prescriptions.…”
Section: Prophylactic Use Of Antimicrobialsmentioning
confidence: 99%
See 3 more Smart Citations